Electronic and optical properties of InSe and GaSe materials: Ab initio study - N. Amrane,; Mariam Ahmed Elkasllan,; Khulood Alshehhi,; Fatima Zraydi,; Juwayni Lucman,; Alam Saj,; Basem Abdel Aziz,; Ibrahim Al Ghoul,; M. Benkraouda, (IJRDO-Journal of Applied Science, 2019)
We present first principles calculations of the electronic and optical properties of InSe and GaSe binary semiconductor compounds. Electronic properties (band structure, density of states, electronic charge density) and optical properties (the dielectric function, the refractive index, reflectivity, and coefficient of extinction) are successfully calculated using self-consistent scalar relativistic full potential linear augmented plane wave method (FP-LAPW) within the generalized gradient approximation (GGA). The Perdew–Burke–Ernzerhof (GGA08) generalized gradient approximation was used for the total energy calculations, while the Modified Becke–Johnson (MBJ) was used for the electronic structure calculations since this functional was designed to reproduce as well as possible the exact exchange correlation potential rather than the total energy, and as a result gives significantly improved results such as band gap and electronic structure. We also investigated the electronic properties of the ternary alloy InxGa1-xSe. The virtual crystal approximation (VCA) was adopted to model the alloy. The results are compared with previous calculations and with experimental measurements, we found good agreement with our calculations.